The Effect of Book Tax Differences, Operational Cash Flow to Earnings Persistence - Sri Devi Eka Suherman; Syamsu Alam; Asriani Junaid (Faculty of Economics dan Business, Atma Jaya Makassar University, 2023)
One of the crucial functions of financial reports is to serve as a basis for evaluating performance and representing the condition of financial performance in an organization or company. Accrual financial reports are prepared based on established standards based on accounting principles, while fiscal financial reports are reports prepared based on tax regulations and used by parties with an interest in the tax collection process. The difference in the value of profit in the financial statements after the fiscal reconciliation is carried out for tax purposes based on the provisions of the tax regulations is what gives rise to the term book tax differences in tax analysis. Earnings persistence is current period earnings which reflects earnings in future periods. This study aims to analyze the effect of Book Tax Differences, Operating Cash Flow and Accrued Profits on Profit Persistence in Manufacturing Companies listed on the Indonesia Stock Exchange. The research object for manufacturing companies listed on the IDX for 2017-2021 is with a sample of 10 manufacturing companies selected using the Purposive Sampling technique. The results showed that the higher the large positive book tax differences, the better the company's profit persistence, while for large negative book tax differences, the higher the large negative book tax differences, the lower the earnings persistence. The higher the company's operating cash flow, the higher the profit persistence. the higher the accrual profit, it will not affect the persistence of earnings.